1988
DOI: 10.2527/jas1988.6692147x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Regression and Principal Components Analysis of Puberty and Growth in Cattle

Abstract: Multiple regression and principal components analyses were employed to examine relationships among pubertal and growth characters. Records used were from 424 bulls and 475 heifers produced by a diallel mating of Angus, Brahman, Hereford, Holstein and Jersey breeds. Characters studied were age, weight and height at puberty and measurements of weight and hip height from 9 to 21 mo of age; pelvic measurements of heifers also were included. Measurements of weight and height near 1 yr of age were related most highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
12

Year Published

1991
1991
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 5 publications
(10 reference statements)
2
14
0
12
Order By: Relevance
“…Segundo Baker et al (1988), a análise dos componentes principais pode revelar relações não-identificadas previamente, contribuindo para melhor interpretação dos dados.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Segundo Baker et al (1988), a análise dos componentes principais pode revelar relações não-identificadas previamente, contribuindo para melhor interpretação dos dados.…”
Section: Introductionunclassified
“…Nesse contexto, a análise de componentes principais deve contribuir na interpretação das relações entre as variáveis e consequentemente nas decisões (Baker et al, 1988;Roso & Fries, 1995).…”
Section: Introductionunclassified
“…Essa prática pode não ser a mais apropriada em um sistema de criação extensivo, haja vista a inclusão da altura do posterior (ALT) nos critérios de seleção, como boa alternativa para controlar o tamanho dos animais. A característica ALT é de fácil mensuração e menos susceptível às variações de meio ambiente e reflete melhor o tamanho corporal quando comparada à medida de peso vivo do animal (Baker et al 1998). Alguns autores (Vargas et al, 1998(Vargas et al, , 2000Riley et al, 2002;Silva et al, 2003) estimaram herdabilidades de magnitude moderada à alta para a ALT, em animais zebuínos, variando de 0,30 a 0,87.…”
Section: Introductionunclassified
“…Baker et al (1988) considered that hip height is the most convenient way to describe the skeleton size in beef cattle. Although Pereira et al (2010) found high positive correlations between growth traits and hip height, the authors concluded it had little influence on the reproductive performance of Nelore heifers.…”
Section: Discussionmentioning
confidence: 99%